(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
There is a significant demand for cylindrical cells, particularly those with the 18650 sizes, in the field of power electronics and electric vehicles application. Charge/discharge rates and battery temperature significantly affect cell performance. The effectiveness of different approaches for evaluating the temperature effect is assessed across diverse charge/discharge rate. This study explores the experimental cycle test of lithium-ion cells from a handheld vacuum cleaner utilizing accelerated tests to evaluate their second life. A pair of new lithium-ion batteries (LIBs) and a pair of second life batteries produced by Murata model US186505D were subjected to tests to verify the state of charge. The findings indicated a decline in performance relative to the manufacturer’s specified nominal capacity. The state of health (SOH) for new batteries varied from 93.66% to 83.59% of their initial capacity. Second-life batteries maintained a SOH between 66.22% and 75.40% of their original capacity. The relatively elevated values render second-life batteries appropriate for less rigorous applications. An evaluation is undertaken on how well the battery performs under varied C-rate currents and 25°C ambient temperatures. The paper focuses on analysing battery cell performance and identifying as well as validating the variation in battery capacity over battery cycle. All tests were conducted using a battery tester software, BK Precision. These results will greatly aid in estimating second life batteries (SLBs) effectively.